THE OCCURRENCE OF POTENTIALLY HARMFUL MOTHS IN SOMBOR AND ČELAREVO (SERBIA) IN 2016 AND FORECAST FOR 2017 (Acta Entomologica Serbica, 2017)
A light trap, type RO Agrobečej, was used in 2016 for recording the presence of moths at localities in Sombor and Čelarevo. The trap was operational from the beginning of April to mid-October. Altogether over 38000 moths were collected. More than 180 species were identified. A significantly smaller frequency of moth species, in comparison to multi-annual averages, was recorded for the species Loxostege sticticalis, Ostrinia nubilalis, Autographa gamma, Helicoverpa armigera, Spodoptera exigua, Agrotis ipsilon, A. segetum and Hyphantria cunea. The number of recorded specimens of the species Lacanobia oleracea was below average in Sombor, but above average in Čelarevo. A significantly larger number of moths, compared to multi-annual averages, was recorded for the species Mamestra brassicae and Agrotis exclamationis. According to Mészáros (1963), the brood coefficient was more than 1 for the species Lacanobia oleracea, A. exclamationis, A. segetum and H. cunea. For these species, there is a positive forecast for 2017. Damage caused by the first brood can be expected from L. oleracea on crucifer and sugar beet production, A. exclamationis on late sown corn, and also on watermelon, crucifers, pepper, tomato and eggplant when seedlings are taken outdoors. The abundance of H. cunea is low, so damages from the first brood are expected on mulberry and walnut. The numerousness of A. segetum is low, so no significant damages are expected, i.e. damages in 2017 can occur only locally.